Elites are people, too: The effects of threat sensitivity on policymakers’ spending priorities - Arceneaux, Kevin; Dunaway, Johanna; Soroka, Stuart (PloS one, 2018)
Recent research suggests that psychological needs can influence the political attitudes of ordinary citizens, often outside of their conscious awareness. In this paper, we investigate whether psychological needs also shape the spending priorities of political elites in the US. Most models of policymaking assume that political elites respond to information in relatively homogeneous ways. We suggest otherwise, and explore one source of difference in information processing, namely, threat sensitivity, which previous research links to increased support for conservative policy attitudes. Drawing on a sample of state-level policymakers, we measure their spending priorities using a survey and their level of threat sensitivity using a standard psychophysiological measure (skin conductance). We find that, like ordinary citizens, threat sensitivity leads even state-level policymakers to prioritize spending on government polices that are designed to minimize threats.